Review of the harvestfishes, genus Peprilus (Perciformes: Stromateidae), of the Atlantic coast of South America - Marceniuk, Alexandre P.; Caires, Rodrigo; Siccha-Ramirez, Raquel [UNESP]; Oliveira, Claudio [UNESP] (Magnolia Press, 2016)
Currently, seven valid species are recognized in the genus Peprilus. Found from United States to Argentina, Peprilus paru has a complex nomenclatural history, with seven junior synonyms, three from North America and four from South Amer-ica. As there has been no recent research, it remains unclear whether species representatives in the north-south axis rep-resent different populations of a single species or distinct species. By comparison of type specimens as well as a comprehensive collection of non-type specimens, this paper aims to clarify the taxonomic status of the nominal species listed as junior synonyms of Peprilus paru in the Atlantic side of South America. Based on morphological data and DNA barcoding, Peprilus crenulatus Cuvier, 1829 and P. xanthurus (Quoy & Gaimard, 1825) are resurrected, while Rhombus argentipinnis Cuvier, 1833 and Rhombus orbicularis Guichenot, 1866, are considered to be junior synonyms of P. crenu-latus.
Keywords: Atlantic coast of South America; Biodiversity; Junior synonyms; Peprilus crenulatus; Peprilus xanthurus; Redescription